3. Rozwiąż równania:
a) – 3x + 4 = -5x - 1
b) - (2x - 1) = 4
c) 3/4(2 – 3x) = -6
d) x2 - (x-3)(x - 1) = 1
e)
2x+3:5 = 2-x:3+ x​


Odpowiedź :

Odpowiedź:

a) - 3x+4 = -5x-1 / +5x

2x+4 = -1 / -4

2x = - 5 / :2

x = - 2,5

b) -(2x-1) = 4

-2x+1 = 4 / -1

-2x = 3 / :(-2)

x = -1,5

c) 3/4(2-3x) = -6

3/2-9/4x = -6 / -3/2

-9/4x = - 15/2 / :(-9/4)

[tex]x = \frac{3}{10} [/tex]

d) 2x-(x-3)(x-1) = 1

2x-(2x-x-3x+3) = 1

2x-2x+x+3x-3 = 1

4x-3 = 1 / +3

4x = 4 /:4

x = 1

e) 2x+3/5) = 2-x:3+x

2x+3/5 = 2-1/3x+x

2x+3/5 = 2+2/3x / - 2/3x

4/3x+3/5 = 2 / - 3/5

4/3x = 7/5 /:4/3

x = 21/20

[tex] x = 1 \frac{1}{20} [/tex]

Powinno być dobrze, za błędy z góry przepraszam